Pengembangan Model Pembelajaran Problem Based Learning Berbantu Aplikasi PISS KTB untuk Meningkatkan Berpikir Kritis Mahasiswa - Ahmad Sodikin Ahmad; Ahmad Ulin Ni’am; Suhartono (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
Educational institutions entering the industrial era 4.0 are required to produce a generation of the nation's children who are knowledgeable, able to think critically, innovate, use information and communication technology as well as daily experiences in society as the core of learning. In practice, many universities have not specially prepared their students for the challenges of the industrial era 4.0, through the lessons they have designed. Based on this thought, the researcher wants to develop a Problem Based Learning learning model assisted by the Piss KTB application. The problem based learning model assisted by the PISS KTB application is included in the category of valid learning models and can be applied in the PAI student class, especially in fiqh subjects. The following are some of the requirements that must be fulfilled: 1. There is an internet network that can be accessed by students and lecturers. 2. Students have cellphones / laptops that have the PISS KTB application installed. 3. Lecturers are able to operate the PISS KTB application, 4. Lecturers are able to understand Arabic texts. While the effectiveness of the problem based learning model is very visible, it is proven by the increasing in student learning outcomes.